Integration of ESG Principles in Social and Sustainable Entrepreneurship: An Innovative Solution - Ida Ayu Putu Ayunda Aprilia Sugiantari (Journal of Applied Accounting, 2026)
The key challenge facing the world today is the difficulty in harmonizing environmental and business sustainability, social responsibility, and financial success. This study aimed to tackle this issue by combining social entrepreneurship with sustainable entrepreneurship to promote the adoption of ESG (Economy, Social, and Governance) principles in creative business models. The research utilized a qualitative method through case study analysis to examine the integration of social entrepreneurship with sustainable entrepreneurship. The findings indicate that this integration can address challenges like constrained funding, profit sharing with social benefits, and enhancing environmental sustainability. Blending the benefits of each method results in a business model that is robust, resilient, and responsive to international challenges. In general, this integration aids businesses in generating lasting value while supporting the attainment of sustainable development objectives. This research determines that social entrepreneurship and sustainable entrepreneurship is a strategic approach to enhance ESG principles in business. Recommendations are offered for business owners to implement this integration idea in their business. Keywords: ESG, Sustainable, Social Entrepreneurship